BRCA mutation carriers suffering from ovarian cancer as a model for treatment decision in higher lines - Place for platinum reinduction - Zikan, Michal; Vecerova, Livia; Dubova, Olga; Sehnal, Borek; Soukupova, Jana (Journal of cancer research and therapeutics, 2023)
ABSTRACT Context: Ovarian carcinoma is a malignancy with the highest mortality among gynecological cancers. Mutations in BRCA1/2 genes are believed to be a favorable prognostic factor and that, in general, the biological behavior of ovarian cancer in BRCA-positive individuals differs from others. However, some clinically relevant issues (i.e., prediction of response to chemotherapy and treatment of platinum-resistant BRCA-positive patients) remain unclear. Aims: (1) The aim of this study was to examine the prevalence of germline BRCA mutations in unselected recurrent ovarian cancer patient population, (2) analyze whether biological behavior of BRCA-positive tumors differs from others, and (3) analyze the effect of platinum reinduction in platinum-resistant BRCA-positive patients. Settings and Design: This was a single-institution retrospective analysis. Subjects and Methods: Consecutive recurrent ovarian cancer patients from years 2012 to 2020 were included; their BRCA1/2 mutational status was analyzed and correlated with progression-free survival (PFS), type of treatment, and response to treatment. Statistical Analysis Used: Statistical significance of differences between and among patients was tested for continuous variables by the Mann-Whitney U-test or the Kruskal-Wallis test; a maximum likelihood Chi-square test was used for categorical variables. Results: Two hundred and forty-three recurrent ovarian cancer patients were included. The median follow-up was 37 months. Pathogenic mutation in BRCA1 or BRCA2 gene was found in 18.1% of patients. There was no difference in PFS comparing BRCA-positive to BRCA-negative patients (median PFS: 10.2 vs. 10.1 months, P = 0.874); there was a difference in PFS comparing BRCA-negative versus BRCA-positive platinum-sensitive patients (9.4 vs. 14.3 months, P = 0.002). BRCA-positive platinum-resistant patients reinduced with platinum achieved a median PFS of 8 months (compared to those receiving nonplatinum treatment, median PFS: 4 months, P = 0.062). Conclusions: Germline BRCA mutations are not exclusive to platinum-sensitive ovarian cancer patients; even in platinum-resistant patients, mutation can be detected. We found no difference in PFS for platinum-sensitive BRCA-positive and BRCA-negative patients. Platinum reinduction may be considered for BRCA-positive platinum-resistant ovarian cancer patients to prolong PFS. Even these data describe only a small population, it supports the clinical practice of platinum-based chemotherapy use in platinum-resistant BRCA-positive patients.